2016
DOI: 10.1016/j.ijrobp.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Initial Report of NRG Oncology/RTOG 0232: A Phase 3 Study Comparing Combined External Beam Radiation and Transperineal Interstitial Permanent Brachytherapy With Brachytherapy Alone for Selected Patients With Intermediate-Risk Prostatic Carcinoma

Abstract: P Z 0.0016). Within the 100 genes, enriched biological functions relate to clusters of genes governing protein degradation, RNA processing, apoptosis, the cell cycle, ATP synthesis, and a large cluster of genes relating to protein localization. Conclusion: We have identified three novel intrinsic subtypes of prostate cancer in the largest study of its kind, and validated our findings across sequencing platforms, storage methods, and within both retrospective and prospective cohorts. In defining unique biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…Follow‐up was short and an older definition of PSA failure (ASTRO) was used. The RTOG study also found that EBRT slightly increased toxicity in patients with one intermediate‐risk factor . Findings are consistent with previous studies that found that dose but not the addition of EBRT predicted FfBF .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Follow‐up was short and an older definition of PSA failure (ASTRO) was used. The RTOG study also found that EBRT slightly increased toxicity in patients with one intermediate‐risk factor . Findings are consistent with previous studies that found that dose but not the addition of EBRT predicted FfBF .…”
Section: Discussionsupporting
confidence: 89%
“…The American Brachytherapy Society consensus guidelines recommend monotherapy brachytherapy in low‐risk patients but regimens for intermediate‐risk patients are less well defined . Recently, the Radiation Therapy Oncology Group (RTOG) conducted a randomized study of patients with prostate cancer with one intermediate‐risk factor treated with implant only or implant and EBRT . Their results indicated equivalence in freedom from biochemical failure (FfBF), overall survival, distant metastasis rate, and prostate cancer‐specific mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Brachytherapy, which is highly conformal therapy, appears to have lower SPC risk than EBRT. 607 The results of this study are expected to clarify the role of EBRT in men receiving permanent seed brachytherapy. In the early 1990s, palladium-103 ( 103 Pd) was introduced.…”
Section: Brachytherapymentioning
confidence: 89%
“…These include the randomized clinical trials performed at the Schiffler Cancer Institute (n=630), 35,36 and the RTOG 0232 study (n=588). 37 Each demonstrated that sEBRT did not improve progression-free or overall survival (REF: ASTRO 2016 PLENARY – Need IJROBP supplemental ref – CURRENTLY EMBARGOED).…”
Section: Multi-parametric Magnetic Resonance Imagingmentioning
confidence: 99%